Fetal brain hemodynamics in pregnancies at term: correlation with gestational age, birthweight and clinical outcome. (19th March 2021) - Ciardulli, Andrea; D'Antonio, Francesco; Caissutti, Claudia; Manzoli, Lamberto; Flacco, Maria Elena; Buongiorno, Silvia; Saccone, Gabriele; Rosati, Paolo; Lanzone, Antonio; Scambia, Giovanni; Berghella, Vincenzo
Abstract: Introduction: The primary aim of this study was to ascertain the strength of association between cerebral blood flow assessed in anterior (ACA), middle (MCA), and posterior (PCA) cerebral arteries and the following clinical outcomes: small for gestational age (SGA), induction of labor (IOL) for oligohydramnios and caesarean section (CS) for nonreassuring fetal status (NRFS) during labor. Material and methods: Retrospective analysis of prospectively collected data on consecutive singleton pregnancies from 40 0/7 to 41 6/7 week of gestation. UA, ACA, MCA, PCA pulsatility index (PI) were measured from 40 weeks of gestations. Furthermore, the ratios between cerebral blood flow and UA (CPR, ACA/UA and PCA/UA) were calculated and correlated with the observed outcomes. Results: Two hundred twenty-four singleton pregnancies were included in the study. Mean PI of either ACA ( p = .04), MCA ( p = .008), and PCA ( p = .003) were lower in the SGA compared to non-SGA group; furthermore, mean PCA PI was significantly lower than MCA PI ( p = .04). Furthermore, CPR ( p = .016), ACA/UA ( p = .02), and PCA/UA ( p = .003) were significantly lower in the SGA group compared to controls. UA, ACA, MCA, and PCA PI were higher in women undergoing IOL for oligohydramnios compared to controls. Logistic regression analysis showed that CPR and PCA/UA ratio were independently associated with SGA. SGA, ACA PI, and ACA/UA were independently associated with CS for NRFS. Finally, birthweight centile, were independently associated with IOL oligohydramnios. Despite this, the predictive accuracy of Doppler in detecting any of the explored outcome was only poor to moderate. Conclusion: Redistribution of cerebral blood flow at term is significantly associated with SGA, IOL for oligohydramnios and CS for NRFS in labor. However, the predictive accuracy of Doppler at term is only poor to moderate, thus advising against its use in clinical practice as a standalone screening test for adverse perinatal outcome in pregnancies at term. Key Message Redistribution of cerebral blood flow at term is significantly associated with SGA, IOL for oligohydramnios and CS for NRFS in labor.